Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1021/es950221i
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Trace Metals in Lakes Superior, Erie, and Ontario

Abstract: In spite of continuing large inputs from anthropogenic sources, average concentrations of many trace metals in the Great Lakes remain quite low: 2.8-4.5 ng L -1 for Cd, 3.2-11 ng L -1 for Pb, and 87-277 ng L -1 for Zn. These metals are rapidly scavenged by the seston (suspended particulates) and have a rapid turnover rate in the water column. Factors that affect the distribution of dissolved trace metals include water depth, seston abundance, and biological processes. Higher concentrations are generally found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
97
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 32 publications
(54 reference statements)
6
97
0
Order By: Relevance
“…The most conservative interpretation of our results is that even very small P-induced growth demands of only about 0.1 d Ϫ1 (doubling time ϳ7 d) cannot be met by the available iron. Dissolved iron in Lake Superior is highly dynamic in space and time (Nriagu et al 1996). In particular locations, there is a pronounced spatial gradient from nearshore to offshore, with concentrations in excess of 100 nmol L Ϫ1 near river outflows but consistently low concentrations of Ͻ5 nmol L Ϫ1 offshore (Sherrell et al unpubl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most conservative interpretation of our results is that even very small P-induced growth demands of only about 0.1 d Ϫ1 (doubling time ϳ7 d) cannot be met by the available iron. Dissolved iron in Lake Superior is highly dynamic in space and time (Nriagu et al 1996). In particular locations, there is a pronounced spatial gradient from nearshore to offshore, with concentrations in excess of 100 nmol L Ϫ1 near river outflows but consistently low concentrations of Ͻ5 nmol L Ϫ1 offshore (Sherrell et al unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…Several early studies of Lake Superior pointed to the potential importance of bioactive metals to algal dynamics (Schelske et al 1972;Shapiro and Glass 1975). The possibility of metal limitation in the Laurentian Great Lakes was made even more compelling through the work of Nriagu et al (1996), who used metal-clean techniques and reported far lower concentrations of trace metals than previous, probably contaminated, studies (Table 1). Coincident with the work reported here, we used highly sensitive analytical techniques (Field and Sherrell 2003) to determine trace metal concentrations in Lake Superior (Table 1).…”
mentioning
confidence: 99%
“…Less in known about the fate of trace metals, except those involved in redox cycles linked to photoreduction that has been extensively investigated (McMahon, 1969;Emmenegger et al, 2001). There is a large body of literature on trace element geochemistry in temperate lakes (e.g., Hamilton-Taylor and Willis, 1990;Noel et al, 1990;Balistrieri, 1992;Viollier et al, 1995Viollier et al, , 1997Hamilton-Taylor et al, 1996Nriagu et al, 1996;Falkner et al, 1997;Albe´ric et al, 2000), including detailed seasonal observations. However the diurnal patterns of trace metal concentration remain poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Both species are isolated from Lake Erie and represent important classes of primary producers that have been documented in the North American Great Lakes (Munawar and Munawar 1982). The current study was carried out to complement ongoing field studies in Lake Superior, an extremely P-deficient aquatic system (Sterner et al 2004;Anagnostou 2005;Anagnostou and Sherrell 2008) in which Zn cycling has been shown to be particularly intense (Nriagu et al 1996;Sherrell unpubl.). The principal goals of this work are two fold: 1) to investigate how phosphate bioavailability regulates phytoplankton metal quotas for seven bioactive elements (Fe, Mn, Co, Ni, Cu, Zn, and Cd); and 2) to determine whether this regulation is similar or different in a representative eukaryote vs. a cyanobacterium, examples of groups that evolved in very different periods of Earth's geochemical history (Falkowski et al 2004) and have different overall mean metal requirements and metal toxicity sensitivities (Saito et al 2003).…”
mentioning
confidence: 99%